Case Report: Rhinosporidiosis Literature Review (2021)
Rhinosporidiosis is caused by Rhinosporidium seeberi, a pathogen currently considered a fungus-like parasite of the eukaryotic group Mesomycetozoea. It is usually a benign condition, with slow growth of polypoid lesions, with involvement of the nose, nasopharynx, or eyes. The clinical characteristics of a painless, friable, polypoid mass, usually unilateral, can guide the diagnosis, but the gold standard for diagnosis is histopathological findings. This article reviews the epidemiology, pathobiology, clinical manifestations, diagnostic strategies, and treatment approach for rhinosporidiosis.